Bile acid-lowering properties of Lactobacillus plantarum Sanriku–SU3 isolated from Japanese surfperch fish. (1st June 2016) - Kuda, Takashi; Masuko, Yurie; Kawahara, Miho; Kondo, Saya; Nemoto, Maki; Nakata, Toru; Kataoka, Manami; Takahashi, Hajime; Kimura, Bon
Abstract: In vitro bile acid-lowering capacity of lactic acid bacteria (LAB) strains (ten Lactobacillus plantarum, four Lactococcus lactis, and two Leuconostoc mesenteroides ) isolated from fermented fish and fish intestine were compared with those of type strains. Among the isolated strains, Lb. plantarum Sanriku–SU3, Lc. lactis Suzuki 8, and Ln. mesenteroides BF6, isolated from Japanese surfperch, Japanese seabass, and Korean rockfish, respectively, clearly showed bile acid-lowering capacity. Although Lc. lactis Suzuki 8 and Ln. mesenteroides BF6 showed activity on deoxycholic and taurocholic acid media, respectively, rather than glycocholic acid, Lb. plantarum Sanriku–SU3 showed the lowering capacity with all of the three cholic acids. These capacities were higher with heat-killed cells than live cells. Plasma cholesterol in mice fed heat-killed cells of Lb. plantarum Sanriku–SU3 tended to be low, while liver cholesterol and plasma glucose were lowered in mice fed live Sanriku–SU3 cells. These results suggest that live as well as heat-killed Lb. plantarum Sanriku–SU3 could ameliorate metabolic syndrome.